Identity and cultural memory in Cvit razgovora naroda i jezika iliričkoga aliti rvackoga (The Flower of conversation of Illyrian or Croatian people and language) (1747) by Filip Grabovac - Šutalo, Goranka (Array, 2019)
This article deals with the textual construction of identity and the strategy of remembrance in Cvit razgovora naroda i jezika iliričkoga aliti rvackoga [The Flower of Conversation of Illyrian or Croatian people and language] (1747) by Filip Grabovac. Using the imagological analytical apparatus, the phenomenon of constituting confessional (Catholic) identity and (dominant Eastern Orthodox) alterity is discussed. The analysis focuses on textual construction or representation of confessional identities, or alterities, wherein numerous value-charged expressions are present. Given the importance of the sociohistorical context in imagological research, the paper takes into account not only the history of literature, but also the history of culture. In addition to imagological treatment, Grabovac’s text is also examined within the framework of cultural memory; discursive strategies of remembrance which maintain the constructed identity are analysed, firm reference points of memory and symbolic figures to which memory adheres are identified.